EVALUATION OF THE ASSOCIATION AMONG YIELD AND CONTRIBUTING CHARACTERS THROUGH PATH COEFFICIENT ANALYSIS IN ADVANCED LINES OF DURUM WHEAT UNDER DIVERSE CONDITIONS - Sh. Heidari; R. Azizinezhad; R. Haghparast; P. Heidari (Journal of Animal and Plant Sciences, 2019)
The present study was carried out at Sararood Dryland Agricultural Research Institute (DARI), during the growing season 2011-13 under rain-fed and irrigated conditions to investigate association among yield and yield contributing characters and to determine the suitable selection criteria in durum wheat breeding for higher yields. Field experiments were performed in a triplicated randomized block design. Combined analysis of variance revealed significant differences between lines for the most of traits studied. Traits of the number of fertile stems (NFS), number of grains per spike (NGPS) and thousand-kernel weight (TKW) were not affected by conditions × lines interaction effects. According to the stepwise regression analysis NFS and NGPS entered in the model and were recognized as the most effective traits on durum wheat grain yield under both irrigated and rain-fed conditions. Whiles NFS and NGPS have been recommended as selection criteria for increasing yield of durum wheat only in the rain-fed condition based on the result of path analysis and indirect effects. Advanced Wheat Line (ADWL)-3, ADWL-8, ADWL-10 and ADWL-7 are suggested useful considering production of desirable NFS, and ADWL-12 and ADWL-16 considering production of desirable NGPS, for further breeding programs and commercial release in the rain-fed condition. Days to physiological maturity (DM) has been recommended as a selection criterion only in the irrigated condition. ADWL-5 and ADWL-1 were selected considering maximum number of DM whiles these lines can adjust their buffered state in response to environmental fluctuations in such a way that they give maximum economic grain yield.
Keywords: durum wheat; morpho-physiological characters; correlation analysis; path analysis; diverse conditions